The Influence of Service Features, User Interface, and Security on User Interest in Wondr Mobile Banking by BNI with Digital Trust as an Intervening Variable (Case Study of the Wondr BNI Application) - Prastiyo, Krisna; Wibowo, Arief (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyse the influence of service features, interface appearance, and security on user interest in the Wondr by BNI mobile banking application, with digital trust as an intervening variable. This study uses a quantitative approach with a survey method, involving 115 respondents selected through purposive sampling. Data were collected through a Likert scale-based questionnaire and analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method. The results indicate that service features and security significantly influence digital trust but do not significantly influence user interest. The interface does not significantly influence digital trust but does influence user interest. The role of digital trust in mediating the influence between service features, interface design, security, and user interest is not significantly influential. The research model shows moderate predictive relevance, with significant influence on the structural model. This study provides important insights into service features, interface design, security, and digital trust that influence user interest in mobile banking applications, particularly in the Wondr by BNI application.